Skin tribology in sport. Issue 3 (7th July 2021) - MacFarlane, Maxwell James; Theobald, Peter
Abstract: This review describes the principles of skin friction and wear for the benefit of sports scientists, engineers and clinicians. Skin exhibits complex behaviour, defying tribological laws for dry contact; hence, its friction and wear characteristics are affected by sliding speed, normal load, and contact area. Some sports seek to increase skin friction to enhance performance; however, this needs to be offset against injury risk given that skin abrades when slid across a rough and hard surface, delaminates when slid across a smooth and hard surface, and chafes or blisters when repeatedly rubbed against some fabrics. Whilst skin interactions can both define and hinder athlete performance, there exists a need to better understand skin biomechanics to optimise the balance of risk versus reward.